2014
DOI: 10.1038/ncomms5572
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAc-mediated interaction between VER2 and TaGRP2 elicits TaVRN1 mRNA accumulation during vernalization in winter wheat

Abstract: Vernalization, sensing of prolonged cold, is important for seasonal flowering in eudicots and monocots. While vernalization silences a repressor (FLC, MADS-box transcription factor) in eudicots, it induces an activator (TaVRN1, an AP1 clade MADS-box transcription factor) in monocots. The mechanism for TaVRN1 induction during vernalization is not well understood. Here we reveal a novel mechanism for controlling TaVRN1 mRNA accumulation in response to prolonged cold sensing in wheat. The carbohydrate-binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
136
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 66 publications
4
136
0
Order By: Relevance
“…These results confirmed that TaGRP2 functions as a flowering repressor (21). Our REMSA results show that the presence of three SNPs in the RIP-3 VRN-D4 region is sufficient to disrupt the binding between TaGRP2 and its target site (Fig.…”
Section: Vrn-d4 Provides Insights Into the Regulation Of Vernalizationsupporting
confidence: 74%
See 3 more Smart Citations
“…These results confirmed that TaGRP2 functions as a flowering repressor (21). Our REMSA results show that the presence of three SNPs in the RIP-3 VRN-D4 region is sufficient to disrupt the binding between TaGRP2 and its target site (Fig.…”
Section: Vrn-d4 Provides Insights Into the Regulation Of Vernalizationsupporting
confidence: 74%
“…4). TaGRP2 binding to the VRN1 pre-mRNA is required for the inhibition of VRN1 expression (21), so the disruption of this interaction can explain the earlier expression of VRN-D4. This mechanism is also consistent with the spring growth habit associated with large deletions in the first intron of VRN1, including the RIP-3 region (20,68).…”
Section: Vrn-d4 Provides Insights Into the Regulation Of Vernalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Chromatin in the first intron of VRN1 has histone modifications that are thought to maintain an inactive transcriptional state, potentially explaining the role of the first intron in maintaining repression of VRN1 before winter 14 . Sequences in the first intron might also regulate processing of the VRN1 transcript 15 . Several active alleles of VRN1 with deletions or insertions in the first intron have been identified in barley [16][17][18][19] .…”
mentioning
confidence: 99%